meningkatkan Kosakata dan Prestasi Akademik melalui Pembelajaran Kelompok di Kalangan Siswa Sekolah Dasar EFL: sebuah studi di sebuah sekolah dasar di semarang - Santoso, Lutfia Aulia; Ambarini, Ririn; Wahyu Widiyanto, Muhammad (Linguistic, English Education and Art (LEEA) Journal, 2025)
This mixed-method study explores the impact of group learning on vocabulary acquisition and English academic performance among sixth-grade primary school students. While vocabulary knowledge is foundational to language competence and overall academic achievement, traditional instruction methods often rely on rote memorization, which may not align with young learners' cognitive and social development. Drawing upon Sociocultural Theory (Vygotsky), Cooperative Learning Theory (Slavin), and Vocabulary Acquisition Theory (Nation), this study positions vocabulary learning as a socially mediated process best facilitated through structured group interaction. A quasi-experimental design with pre- and post-tests was employed to compare vocabulary retention between a group-based learning cohort (n = 30) and a control group receiving traditional instruction (n = 30). Complementary qualitative data were collected via focus group discussions and in-depth interviews. Quantitative results revealed a statistically significant improvement in the experimental group’s vocabulary and English performance scores. Thematic analysis identified key mechanisms of group learning effectiveness, including peer support, motivation, active participation, and confidence-building. Findings indicate that group learning not only enhances lexical retention but also fosters a psychologically safe and motivationally rich environment for language development. Moreover, low-performing and introverted students exhibited disproportionate gains, suggesting the inclusivity and adaptability of group learning strategies. This study contributes to the limited body of empirical research on collaborative vocabulary instruction in Southeast Asia and offers practical implications for curriculum design, teacher training, and inclusive language pedagogy in primary education. Keywords: Collaborative Learning, Group Learning, Peer Scaffolding, Primary Education, Student Motivation